Stationary Bandits, State Capacity, and the Malthusian Transition : The Lasting Impact of the Taiping Rebellion - Xu, L. Colin (World Bank, Washington, DC, 2018)
The Taiping Rebellion (1851-1864) in China was the deadliest civil war in history. This paper provides evidence that this cataclysmic event significantly shaped the Malthusian transition and long-term development that followed, especially in areas where the experiences that stemmed from the rebellion led to better property rights, stronger local fiscal capacity, and rule by leaders with longer-term governance horizons. More than one and a half centuries after the rebellion’s end, population increases from pre-war levels remain 38 to 67 percent lower in areas that were affected by the rebellion than in those that were unaffected. Moreover, areas that were affected by the rebellion have, on average, greater fiscal capacity and modern economic sectors to the present day. Two channels for the effects of the rebellion are stationary banditry (manifested by varying property rights and the rebellion area's proximity to the Taiping capital), and the wartime strengthening of fiscal capacity. The analysis shows evidence of complementarity between wartime state capacity and local institutions, and of the long-term benefits of fiscal decentralization in a large country. Furthermore, initial human capital is strongly associated with long-term development.